The Effect of Separating Authorities on the Relationship between these Authorities in the Iraqi Constitution 2005 - Jameel , Ahmed Mehsen (International Journal of Psychosocial Rehabilitation, 2020)
When we ask about the relationship between legislative and executive authorities, and ask again inversely what's the relationship between executive and legislative authorities, the answer here is not one and things aren't similar, where the legislative-executive authorities relationship has features that differ from the executive-legislative authorities relationship. It is not just advancing and delaying. The Iraqi constitution in item 47 stated that federal authorities consist of legislative, executive and judicial authorities and depend in practicing their specialties and duties on authorities separation dogma, but when reviewing these authorities duties in the constitution, we find a lot of common duties between federal authorities; so, any authority can't achieve them alone. This would indicate that the correct conception of authorities separation dogma in the Iraqi constitution, especially, doesn't affect their cooperative work and does not limit it to call for the isolation between these authorities to activate separation.